“Escritura sin límites”: material didáctico digital para el fortalecimiento de la escritura argumentativa en estudiantes de español como lengua extranjera en un nivel B2 (2023)
The objective of this research is to desing and implement a digital didactic material to help students at Federal University of Ouro Petro, Brazil, improve their writing skills in Spanish as a foreign language through virtual sessions. There is a need for students to advance from level B1 to level B2 according to the Common European Framework, which will enable them to write clear and detailed texts on a wide variety of topics and to produce compositions or reports that support or refute a specific point of view.